1993
DOI: 10.1203/00006450-199312000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fluidity of Polymorphonuclear Leukocytes from Children with Primary Ciliary Dyskinesia

Abstract: ABSTRACT. Plasma membrane fluidity and heterogeneity of polymorphonuclear leukocytes (PMN) were investigated in seven children with primary ciliary dyskinesia (PCD) and 17 healthy controls. Membrane fluidity and heterogeneity were studied by measuring the steady state fluorescence anisotropy and fluorescence decay of 1-(Ctrimethylammoniumphenyl)d-phenyl-1,3 J-hexatriene (TMA-DPH) incorporated into PMN plasma membrane. Our results show an increase in membrane fluidity at the surface level of PMN from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Conceivably, CCDC39 and CCDC40 may have a role in other nonepithelial cells that affect lung health. Early studies showed that neutrophils extracted from some individuals with PCD may have defective motility causing impaired chemotaxis and bacterial killing (35,36). Because these studies were performed before the advent of genetic testing, it is unclear whether the neutrophil phenotype is related to specific PCD genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, CCDC39 and CCDC40 may have a role in other nonepithelial cells that affect lung health. Early studies showed that neutrophils extracted from some individuals with PCD may have defective motility causing impaired chemotaxis and bacterial killing (35,36). Because these studies were performed before the advent of genetic testing, it is unclear whether the neutrophil phenotype is related to specific PCD genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of abnormalities in the microtubule structure and arrangement in cilia and sperm tails have now been described in patients with primary ciliary dyskinesia (18). While attempts to define microtubule structural abnormalities in patient' s neutrophils that are similar to those seen in cilia and sperm tails have been unsuccessful (7), a functional study of neutrophils from the patients has shown that an integrated cytoplasmic microtubule-membrane interaction is essential for their motility (19).…”
Section: Discussionmentioning
confidence: 99%
“…Primary neutrophils isolated from PCD patients have impaired directed migration to chemokines in in vitro assays ( Afzelius et al, 1980 ; Walter et al, 1990 ; Kantar et al, 1993 ; Cockx et al, 2017 ). Furthermore, microtubule destabilization via nocodazole treatment decreases the ability of neutrophils to migrate appropriately toward a chemical stimulus ( Gundersen and Bulinski, 1988 ; Kadir et al, 2011 ; Yoo et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%